Peran Digital Marketing dalam Upaya Meningkatkan Omset Penjualan Tenun Endek dan Songket Desa Telaga Tawang - Anak Agung Istri Agung Maheswari; Nanda Dwi Azhizah; Ifan Nugraha; Made Pradnyan Hary N (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
One of the livelihoods of the people of Telaga tawang Village is to become an Endek and Songket weaver. However, the community is only a worker because the costs needed to buy weaving equipment and equipment are quite large; because of that, Arta Sedana business owner provides capital in the form of equipment to have a job and earn income. The role of digital marketing to increase the sales turnover of endek and songket weaving, we provide direction on how to promote endek and songket woven products in direct marketing. This promotion can be done through social media such as E-mail, Instagram, Facebook, and WhatsApp. We also help create social media accounts and tell us how to use social media accounts to market products. The method of activity we do is to provide counseling to the Arta Sedana business group by telling them how business opportunities are in utilizing digital marketing. Therefore, the solution we can provide is to provide directions for creating social media accounts or those related to digital marketing.